Retrotransposon Proliferation Coincident with the Evolution of Dioecy in Asparagus. Issue 9 (1st September 2016) - Harkess, Alex; Mercati, Francesco; Abbate, Loredana; McKain, Michael; Pires, J Chris; Sala, Tea; Sunseri, Francesco; Falavigna, Agostino; Leebens-Mack, Jim
Abstract: Current phylogenetic sampling reveals that dioecy and an XY sex chromosome pair evolved once, or possibly twice, in the genus Asparagus . Although there appear to be some lineage-specific polyploidization events, the base chromosome number of 2 n  = 2× = 20 is relatively conserved across the Asparagus genus. Regardless, dioecious species tend to have larger genomes than hermaphroditic species. Here, we test whether this genome size expansion in dioecious species is related to a polyploidization and subsequent chromosome fusion, or to retrotransposon proliferation in dioecious species. We first estimate genome sizes, or use published values, for four hermaphrodites and four dioecious species distributed across the phylogeny, and show that dioecious species typically have larger genomes than hermaphroditic species. Utilizing a phylogenomic approach, we find no evidence for ancient polyploidization contributing to increased genome sizes of sampled dioecious species. We do find support for an ancient whole genome duplication (WGD) event predating the diversification of the Asparagus genus. Repetitive DNA content of the four hermaphroditic and four dioecious species was characterized based on randomly sampled whole genome shotgun sequencing, and common elements were annotated. Across our broad phylogenetic sampling, Ty-1 Copia retroelements, in particular, have undergone a marked proliferation in dioecious species. In the absence of a detectable WGD event, retrotransposon proliferation is the most likely explanation for the precipitous increase in genome size in dioecious Asparagus species.